2019
DOI: 10.1115/1.4042123
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Composite Offshore Wind Turbine Blades Under Operating Conditions

Abstract: World energy demand has increased immediately and is expected to continue to grow in the foreseeable future. Therefore, an overall change of energy consumption continuously from fossil fuels to renewable energy sources, and low service and maintenance price are the benefits of using renewable energies such as using wind turbines as an electricity generator. In this context, offshore wind power refers to the development of wind parks in bodies of water to produce electricity from wind. Better wind speeds are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The composite lamination of the blade is also composed of foam core material (SKINFOAM) whose mechanical properties are indicated in Table 3 33 …”
Section: Conception Of Wind Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…The composite lamination of the blade is also composed of foam core material (SKINFOAM) whose mechanical properties are indicated in Table 3 33 …”
Section: Conception Of Wind Turbinementioning
confidence: 99%
“…Taking into account the gluing between the shear webs and the blade, Figure 8. An isotropic material is added to the structure, its properties are reported in Table 3 33 …”
Section: Conception Of Wind Turbinementioning
confidence: 99%
“…It has a characteristic that favors its massive penetration in the urban environment because solar radiation is received everywhere with levels of intensity that allow the production of electricity (Lopez-Rey et al, 2019), being determinant for this market advance (Rosa et al, 2018). Wind energy is clean, abundant, inexhaustible, and environmentally preferable (Oyedepo, Adaramola, & Paul, 2012) and refers to the development of wind farms near beaches, rivers, or lakes to produce electricity from the wind (Tarfaoui, Nachtane, & Boudounit, 2019). Finally, biomass energy is clean and renewable energy and is also considered an alternative to fossil fuels (Liu, Feng, & He, 2019), as it can contribute significantly to reduce the environmental impacts associated with using waste from other processes for generation, such as the use of residues from olive oil production (Ducom et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis, the strength constraint imposed was the Tsai-Wu failure criterion in order to determine the optimum structural design for the spar caps and webs of two wind turbine blades. Yeh and Wang (2017) used the finite element analysis software Ansys to perform a stress analysis of a 5 MW composite wind turbine blade, where they found that the largest combined load occurred at a 0 • pitch angle, and the stress and displacement are the greatest when the wind blade is located at 120 • angular position from its highest vertex. Zhu and Rustamov (2013) performed a structural analysis, using the finite element method, to evaluate a 750 kW wind turbine blade under various load conditions.…”
Section: Introductionmentioning
confidence: 99%